PENGARUH EKUITAS MEREK TERHADAP PERILAKU KONSUMEN DALAM MELAKUKAN KEPUTUSAN PEMBELIAN PADA SMARTPHONE MEREK IPHONE DI KOTA BATAM - Simanjuntak, Jackhon Pahala; Heryenzus, Heryenzus; Yopi (Jurnal PROFITA : Akuntansi dan Manajemen, 2024)
The purpose of this study was to determine the effect of brand equity on consumer behavior in making purchasing decisions on iPhone brand smartphones in Batam City. This study was conducted using quantitative techniques. The research sample used 100 respondents to consumers in Batam City, especially those who have used iPhone smartphones using the lemeshow formula. The questionnaire was used as a data collection technique. Based on the results of multiple linear regression, brand image (X1) has an influence. After the data was collected, the researchers tested the data using SmartPLS 3.0 software. PLS functions to confirm the accuracy of a theory and build relationships between variables that do not have a theory or proportion. This study proves that there is a significant positive relationship between the variables Brand Equity on Consumer Behavior, Brand Equity on Purchasing Decisions and Consumer Behavior on Purchasing Decisions on iPhone brand smartphones in Batam City.